Competitiveness of the enterprise on the market when developing new production - R. V. Chernov (Вестник университета, 2024)
The purposes of the study are to analyse competitiveness and develop recommendations for improving it when mastering production of new products. When reviewing well-known works where competitiveness has been studied, the author has examined the impact of changes at the macro level on the processes of developing new products by enterprises. In the article, the author has analysed various approaches to determining competitiveness. The influence of unilateral sanctions on competitiveness in the development of new products has been considered. At the same time, it is noted that sanctions as a tool of forceful pressure cannot be used as a tool for increasing success of enterprises in a fair competitive market. Therefore, the author highlights that the classical theory of competitive and non-competitive markets is not fully applicable in the current situation. In the works of some scientists, the competitiveness of an enterprise in the market that does not correspond to present realities has been analysed, and accordingly, such studies are not applicable in the conditions of a necessary fair competitive market. The author has suggested ways to determine both current competitiveness and its indicators in past and future periods. It is proposed to restructure the domestic technology transfer to the international one with friendly countries, moving from simple trade and exchange of goods to joint product development. Conditions are also needed within the country for scaling ideas and new designs. In an uncompetitive market, merging or associating companies for research, development and mastery the production of new products may be one of the ways to circumvent sanctions. Thus, the method is more applicable to technologies with a high level of digital and technological protection in the know-how mode.